COVID-19: Infection or Autoimmunity - Icenogle, Timothy (Frontiers in Immunology, 2020)
The clinical and laboratory features of COVID-19 are reviewed with attention to the immunologic manifestations of the disease. Recent COVID-19 publications describe myocarditis and a hemophagocytic lymphohistiocytosis like syndrome that suggest an over-exuberant autoimmune component of the disease. Yet, the immunosuppressive regimens that have been utilized show little efficacy in COVID-19. Review of the immunology of viral induced Type II and Type IV hypersensitivity reactions reveals why these medications lack efficacy. The disconnect between the immunology literature and clinical understanding is explored. There is potential use of T cell depleting therapies and possibly anti-CD20 therapy for COVID-19 and clinical research using these medications is warranted.